1995
DOI: 10.1152/jappl.1995.79.3.748
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin does not alter natural killer cell response to 2.5 h of running

Abstract: The effect of 2.5 h of treadmill running at 75.6 +/- 0.9% maximal O2 uptake (VO2max) on natural killer (NK) cell cytotoxic activity (NKCA) was investigated in 22 experienced marathon runners (VO2max 57.9 +/- 1.1 ml.kg-1.min-1, age 38.7 +/- 1.5 yr). Blood samples were taken before (0715) and immediately after exercise (1000), with three more samples taken during 6 h of recovery (1130, 1300, and 1600). Ten sedentary controls (VO2max 34.7 +/- 1.0 ml.kg-1.min-1, age 45.3 +/- 2.3 yr) sat in the laboratory during te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…Concurrent with several reports Mitchell et al, 1998;Nieman, Simandle, et al, 1995;Simonson & Jackson, 2004), we observed increases in total leukocyte, lymphocytes, and neutrophils immediately after acute resistive exercise. We did not, however, observe the same magnitude of cell responses with resistive exercise as that reported during endurance exercise.…”
Section: Immune Responsessupporting
confidence: 89%
See 4 more Smart Citations
“…Concurrent with several reports Mitchell et al, 1998;Nieman, Simandle, et al, 1995;Simonson & Jackson, 2004), we observed increases in total leukocyte, lymphocytes, and neutrophils immediately after acute resistive exercise. We did not, however, observe the same magnitude of cell responses with resistive exercise as that reported during endurance exercise.…”
Section: Immune Responsessupporting
confidence: 89%
“…Acute bouts of heavy endurance or resistance exercise have been shown to influence immune cells in the circulating peripheral blood (Henson et al, 1999(Henson et al, , 1998Kraemer et al, 1996;Nieman, 1997;Nieman, Simandle, et al, 1995;Simonson & Jackson, 2004■). Concurrent with several reports Mitchell et al, 1998;Nieman, Simandle, et al, 1995;Simonson & Jackson, 2004), we observed increases in total leukocyte, lymphocytes, and neutrophils immediately after acute resistive exercise.…”
Section: Immune Responsessupporting
confidence: 86%
See 3 more Smart Citations